PEMBUMIAN MISI PROFETIK DI TENGAH ARUS GLOBALISASI PERSPEKTIF ISLAM HUMANIS - Yusdani Yusdani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2011)
Penulis membahas globalisasi yang salah satu karakteristiknya adalah mempertemukan aspek-aspek social menjadi sebuah standar baru. Standar tersebut tidak lepas dari sisi negative yang berimbas pada perubahan social dan budaya. Tulisan ini berkaitan dengan isu humanitarian sebagai dampak negative globalisasi. Cendekiawan muslim perlu memberikan penerangan kepada sosial dengan mengerjakannya juga, hal ini membutuhkan kerangka skema perumusan dari Islam untuk mempertahankan nilai-nalai kemanusiaan. The author of article below tries to discuss that globalization has the characteristics of uniting the social aspects into a new standard for various parts of the world as well as the negative impact toward social and cultural change, dealing with humanitarian issues as the negative impact of globalization, Muslim intellectuals need to provide enlightenment to the society By doing so, it needs to be formulated paradigmatic framework of Islam to defend human values. In this sense, Humanist Islam discourse in the context of scientific development and to formulate strategic steps toward concrete and took a position as a science and a discourse based on prophetic values. Thus, developing and Islamic teaching in Indonesia today is Islamic as a science. So, it needs paradigm shift from the theocentric-eschatological- to anthropocentric transformative.